E-086 Effect of age on cerebral arteriovenous malformation draining vein stenosis. (23rd July 2017) - Shakur, S; Brunozzi, D; Ismail, R; Charbel, F; Alaraj, A
Abstract : Introduction: The pathogenesis of venous intimal hyperplasia and venous outflow stenosis associated with cerebral arteriovenous malformation (AVM) draining veins is poorly understood. We sought to determine the relationship between venous stenosis and age. Methods: All patients with an AVM seen at our institution between 1990–2016 who underwent a diagnostic cerebral angiogram were retrospectively reviewed (n=281). Draining vein stenosis was measured from angiograms prior to any treatment. Relationship between venous stenosis, age, and age class (5 year increments) was assessed using linear regression analysis. Results: 281 patients were included (mean age 39 years, age range 3-83 years, 55% male). Venous stenosis measuring ≥ 50% was present in 59 patients (21% of cohort). Higher percentage stenosis correlated significantly with older age class (R=+0.12, P =0.05) (Figure). Higher percentage stenosis also tended to be associated with older age (R=+0.11, P =0.07) (figure 1). Conclusion: Higher percentage venous stenosis is associated with older age class, suggesting that venous stenosis is a progressive disease that occurs by the same process that leads to intimal hyperplasia. Disclosures: S. Shakur: None. D. Brunozzi: None. R. Ismail: None. F. Charbel: None. A. Alaraj: None.